Arthroscopic subacromial decompression in the treatment of impingement syndrome - (:unkn) unknown (My University, 2003)
During the past decade, arthroscopy has become an accepted tool for the evaluation and management of shoulder disorders. The glenohumeral joint, subacromial space, acromioclavicular joint, and even the scapulothoracic articulation can be assessed through arthroscopy. Proper portal placement allows a safe access without risk for neurovascular, tendon, or articular injuries. Anterior acromioplasty is probably the most common arthroscopic procedure performed in the shoulder, with reported results similar to open techniques. This article focuses on the arthroscopic treatment of impingement syndrome in the light of published data, together with its technical aspects.
Keywords: Humans; Shoulder Impingement Syndrome; Arthroscopy; Acromioclavicular Joint; Acromion